Electronic Transport in Oxidized Zigzag Graphene Nanoribbons. (16th January 2017) - Kolli, Venkata Sai Pavan Choudary; Kumar, Vipin; Shukla, Shobha; Saxena, Sumit
ABSTRACT: The electronic and transport properties of graphene nanoribbons strongly depends on different types of adatoms. Oxygen as adatom on graphene is expected to resemble oxidized graphene sheets and enable in understanding their transport properties. Here, we report the transport properties of oxygen adsorbed zigzag edge saturated graphene nanoribbon. It is interesting to note that increasing the number of oxygen adatoms on graphene sheets lift the spin degeneracy as observed in the transmission profile of graphene nanoribbons. The relative orientation of the oxygen atom on the graphene basal plane is detrimental to flow of spin current in the nanoribbon.